2023
DOI: 10.1039/d3cp04574a
|View full text |Cite
|
Sign up to set email alerts
|

Development of SrWO4:Ho3+/Yb3+ green phosphor for optical thermometry application

Ram Gopal,
Chandni Kumari,
Jairam Manam

Abstract: SrWO4: Ho3+/Yb3+ phosphor exhibiting down-conversion and up-conversion photoluminescence for green light generation and optical thermometry applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Among various inorganic materials, the molybdate-based material ABO 4 (A = Ca, Ba, Sr and B = W, Mo) is widely used in down-conversion phosphors due to its chemical stability and the property of transferring energy absorbed in the UV and visible light regions to activator ions, making it a lanthanide ion. 16–20 It is suitable as a base material for rare-earth (RE)-doped phosphors. Jiang et al introduced the structure and emission characteristics of a Ca 2 MgWO 6 :Er 3+ ,Yb 3+ UC phosphor synthesized by sintering at high temperature using a solid-state reaction (SSR) method and suggested that it can be applied to optical thermometry.…”
Section: Introductionmentioning
confidence: 99%
“…Among various inorganic materials, the molybdate-based material ABO 4 (A = Ca, Ba, Sr and B = W, Mo) is widely used in down-conversion phosphors due to its chemical stability and the property of transferring energy absorbed in the UV and visible light regions to activator ions, making it a lanthanide ion. 16–20 It is suitable as a base material for rare-earth (RE)-doped phosphors. Jiang et al introduced the structure and emission characteristics of a Ca 2 MgWO 6 :Er 3+ ,Yb 3+ UC phosphor synthesized by sintering at high temperature using a solid-state reaction (SSR) method and suggested that it can be applied to optical thermometry.…”
Section: Introductionmentioning
confidence: 99%